Fatores que influenciam o comportamento do consumidor e a intenção de compra de produtos de luxo de segunda mão - Donzelli, Juliana Ribeiro Garcia (2023)
The second-hand luxury goods market (clothing, footwear, leather items, jewelry, watches, and eyewear, purchased through second-hand luxury goods platforms) has been growing worldwide and generated US$ 4.9 billion in sales in 2021. The estimate for the year 2027 is for sales at the level of US$ 14.7 billion (Statista, 2023). Thus, the objective of this study is to examine the effects of social, personal, conspicuous, environmental, and economic factors on the purchase attitude of second-hand luxury products and whether there is an increase in the relationships between subjective norms and perception of control of behavior with purchase intention with the use of anonymity and guarantee of authenticity, in that order. For this model, we considered following constructs: social, personal, conspicuous, environmental, and economic factors, the attitude and intention to purchase second-hand luxury products, anonymity, the guarantee of authenticity, the perception of behavioral control and subjective norms. For the elaboration of each of the constructs and hypotheses of the model, we used a literature review. This research was carried out through a survey, applied to a convenience sample, and use of Structural Equation Modeling for the analysis, conducted through the SmartPLS 4.0 software. The sample is composed of 301 respondents and the results of the analysis show that anonymity and guarantee of authenticity do not increase the relationship between subjective norms and perception of control of behavior with the intention to purchase second-hand luxury items. Moreover, environmental, and personal factors have no positive relationship on purchase attitude of second-hand luxury products. The theoretical contribution brings the evaluation of the factors for buying second-hand luxury items, a context that no study has addressed so far. Therefore, we sought to fill this gap. For the practical context, it is necessary to make more people aware of luxury thrift stores, as 53% of non-consumers said they did not know any about it. This work also presents limitations and propositions for future research.